Clinical practice patterns in indirect peroral cholangiopancreatoscopy: outcome of a European survey - Stassen, Pauline M.C.; de Jonge, Pieter Jan F.; Webster, George J.M.; Ellrichmann, Mark; Dormann, Arno J.; Udd, Marianne; Bruno, Marco J.; Cennamo, Vincenzo; on behalf of the European Cholangioscopy Group; and the German Spyglass User Group (Endoscopy International Open, 2021)
Background and aims Indirect peroral cholangiopancreatoscopy (IPOC) is a relatively new diagnostic and therapeutic tool for biliopancreatic diseases. This international survey aimed to evaluate clinical practice patterns in IPOC among endoscopists in Europe.Methods An online survey was developed comprising 66 questions on the use of IPOC. Questions were grouped into four domains. The survey was sent to 369 endoscopists who perform IPOC.Results 86 respondents (23.3 %) from 21 different countries across Europe completed the survey. The main indications for cholangioscopy were determination of biliary strictures (85 [98.8 %]) and removal of common bile duct or intrahepatic duct stones (79 [91.9 %]), accounting for an estimated use of 40 % (interquartile range [IQR] 25–50) and 40 % (IQR 30–60), respectively, of all cases undergoing cholangioscopy. Pancreatoscopy was mainly used for removal of pancreatic duct stones (68/76 [89.5 %]), accounting for an estimated use of 76.5 % (IQR 50–95) of all cases undergoing pancreatoscopy. Only 13/85 respondents (15.3 %) had an institutional standardized protocol for targeted cholangioscopy-guided biopsy sampling. IPOC with lithotripsy was used as first-line treatment in selected patients with bile duct stones or pancreatic stones by 24/79 (30.4 %) and 53/68 (77.9 %) respondents, respectively.Conclusions This first European survey on the clinical practice of IPOC demonstrated wide variation in experience, indications, and techniques. These results emphasize the need for prospective studies and development of an international consensus guideline to standardize the practice and quality of IPOC.